3D Graphene – sponge skeleton reinforced polysulfide rubber nanocomposites with improved electrical and thermal conductivity. (April 2021) - Tao, Wenjie; Zeng, Shaohua; Xu, Ying; Nie, Wangyan; Zhou, Yifeng; Qin, Pengbo; Wu, Songhua; Chen, Pengpeng
Highlights: PU sponge was used as a template and GO together through hydrothermal reduction prepared RGO-PU with three-dimensional (3D) skeleton. The prepared 3D RGO-PU had obvious reinforcing effect on various properties of PSR. The prepared RGO-PU network had excellent reinforcing effect on electrical and thermal conductivity properties of PSR, which was because that the introduction of 3D RGO-PU foam provided a path for electronic transmission and phonons transfer. Abstract: As high performance sealants, polysulfide rubbers (PSR) have been extensive used to seal the tanks of aircraft fuel. Disappointingly, it is easy to produce static electricity due to the movement of fuel, resulting in security issue. In this work, a three-dimensional (3D) RGO-PU foam was constructed by using PU sponge as a template and GO together through hydrothermal reduction. Then the polysulfide rubber composites (RGO-PU/PSR) were fabricated by impregnating 3D RGO-PU framework with liquid polysulfide oligomers (LPO) under vacuum assistance, following by heat treatment. The RGO-PU/PSR composites exhibited improved conductive properties than neat PSR. For example, the volume resistivity of the 0.5 wt%-RGO-PU/PSR composites was 2.6 × 10 6 Ω·cm, which had a conspicuous 5 orders of magnitude decrease compared to neat PSR. The thermal conductivity of RGO-PU/PSR composite was also enhanced to 0.598 W/(m.k), which raised about 153% compared to the value for neat PSR. It was because that the introduction of 3D RGO-PU foam provided a path for electronic transmission and phonons transfer. In addition, the dielectric properties demonstrated that RGO-PU/PSR composites showed a higher dielectric constant than neat PSR. Furthermore, the polysulfide rubber composites also showed greatly improved compression strength and Young's Modulus.